BIOETIKA DALAM KESEHATAN MASYARAKAT - Gunawan Widjaja (CV. Adiba Aisha Amira, 2026)
Bioethics in public health provides a normative framework that guides health policies, programmes and practices to ensure they are not only technically effective, but also fair, humane and respectful of the rights and dignity of individuals and communities. The application of bioethical principles—autonomy, beneficence, non-maleficence, and justice—demonstrates that public health interventions must balance collective interests with respect for the freedom and justice of every member of society. In the Indonesian context, these ethical dimensions are particularly important given the expansion of health programmes, the digitisation of data, and the emergence of issues such as pandemics and socio-economic inequalities. This literature review examines the concepts and principles of bioethics in public health, as well as their implementation in public health policies, programmes, and practices, including the challenges and recommendations for improvement. The findings highlight the need to strengthen regulations, ethics committees, bioethics education, and community participation to ensure that health development proceeds in an ethical, transparent, and equitable manner.